2001
DOI: 10.1055/s-2001-18486
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Deep Vein Thrombosis in Suspected Pulmonary Embolism

Abstract: Pulmonary embolism (PE) and deep vein thrombosis are two facets of the same disease, that is, venous thromboembolism (VTE). In patients with angiographically proven PE, the prevalence of proximal deep vein thrombosis by venography is around 70%. The sensitivity of compression ultrasonography (US) for the diagnosis of acute VTE in patients with a suspicion of PE is between 40 and 60%, with a high specificity (96 to 100%). Taking into account the 20 to 30% prevalence of PE in a population consulting for suspicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Systematic screening studies by bilateral ascending phlebography of patients who had undergone orthopedic surgery or were hospitalized for medical conditions have demonstrated that asymptomatic DVT of the leg occurs at a rate of 40%–60% [5]. Furthermore, asymptomatic proximal DVT is found in approximately 70% of patients who present clinical symptoms of PE but no overt clinical symptom of DVT in the leg [6]. The post‐thrombotic syndrome is frequently observed in the general population and has been widely assumed to be due to DVT [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic screening studies by bilateral ascending phlebography of patients who had undergone orthopedic surgery or were hospitalized for medical conditions have demonstrated that asymptomatic DVT of the leg occurs at a rate of 40%–60% [5]. Furthermore, asymptomatic proximal DVT is found in approximately 70% of patients who present clinical symptoms of PE but no overt clinical symptom of DVT in the leg [6]. The post‐thrombotic syndrome is frequently observed in the general population and has been widely assumed to be due to DVT [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of two related clinical manifestations: Pulmonary thromboembolism (PTE) and deep venous thrombosis (DVT). [ 1 2 ] DVT of the lower extremities is believed to be the source of PTE in most patients, and the primary risk factor for recurrent PTE is the presence of residual proximal venous thrombosis. Postoperative PTE is more difficult to diagnose compared with a spontaneous PTE because clinical symptoms and signs suggestive of PTE can be explained by the effects of operations, such as incisional pain; hypovolemia; and atelectasis, or might be masked by analgesics, including epidural anesthetics.…”
Section: Introductionmentioning
confidence: 99%